(untitled) (PANGEEA, 2025)
Besides environmental education, the ones for health, anti-drug use, demographic, nutritional, we also add a new branch of education-of great interest to students-the geopolitical education. In the textbooks and curricula between the two World Wars, geopolitical lessons targeted the position of our country among its neighbours, the border issue, the evolution of the Romanian people on its traditional territory, the role of the Carpathians, the Danube and the Black Sea to the Romanian people, Romania’s ethnic map, the unity issue, etc. During communism, the geopolitical elements targeted the glorification of economic and cultural accomplishments of the U.S.S.R. and other socialist countries. After 1990, in Geography curricula and textbooks, the geopolitical lessons diversified, tackling an up-to-date topic: the defining of the state and its components: types of states: the settling and types of borders: internal and external conflicts: the political geography of the seas and oceans: the geopolitics of the Arctic Poles: the role of straits and channels: the economic and geopolitical unions of the world: the areas of political decisions, the organization of the world space. By studying geopolitical lessons, the students got some skills which will allow them to: use scientific new terms in geopolitics and geopolitical geography: use and read geopolitical maps: use the space and time coordinates that make up the world: identify some criteria of making economic and geopolitical unions: understanding the geopolitical coordinate of the nowadays world: using graphics and maps about the geopolitical world system.